The anatomy of the male inferior hypogastric plexus: What should we know for nerve sparing surgery. Issue 6 (24th October 2018) - Röthlisberger, Raphael; Aurore, Valerie; Boemke, Susanne; Bangerter, Hannes; Bergmann, Mathias; Thalmann, George N.; Djonov, Valentin
Abstract : The aim of this study was to investigate the nerve supply to the structures in the male lesser pelvis and review its clinical relevance, especially during nerve sparing surgery. Three formalin‐embalmed and 16 Thiel‐embalmed male hemipelves were used. They were microdissected after repeated treatments with nitric acid diluted 1:10 with milliQ‐water. The inferior hypogastric plexus (IHP) is a fan‐like structure lateral from the rectum on the fascia of the levator ani. Nerves emerging from the proximal, solid part of the plexus follow the internal iliacal vessels and reach the prostate from dorsolateral. The innervation of the urethra and the corpora cavernosa derives from two origins: one follows the ejaculatory duct and the seminal vesicle, reaching the proximal urethra and the prostate from dorsal; the other follows the inferior vesical artery to reach the prostate from lateral, and then forms the neurovascular bundle on both sides of the prostatic fascia, spreading to the pelvic floor muscles and the corpora cavernosa along with the distal urethra. A connection between the two parts was demonstrated in approximately one third of the samples investigated. The nerve supply to the urinary bladder, the urethra, and the corpora cavernosa emerges mainly from the IHP. The innervation of the proximal urethra and its autonomic muscular structures has a dorsal (ejaculatory duct) and lateral (inferior vesical artery) origin. To maintain good erectile and continence function it is important to save both the dorsal and lateral neurovascular roots. Clin. Anat. 31:788–796, 2018. © 2018 Wiley Periodicals, Inc.